2008
DOI: 10.1190/1.2827875
|View full text |Cite
|
Sign up to set email alerts
|

Simulating migrated and inverted seismic data by filtering a geologic model

Abstract: The simulation of migrated and inverted data is hampered by the high computational cost of generating 3D synthetic data, followed by processes of migration and inversion. For example, simulating the migrated seismic signature of subtle stratigraphic traps demands the expensive exercise of 3D forward modeling, followed by 3D migration of the synthetic seismograms. This computational cost can be overcome using a strategy for simulating migrated and inverted data by filtering a geologic model with 3D spatial-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The interferometric PSF has a lot in common with the resolution function or PSF as we find it in seismic migration (Schuster and Hu, 2000;Thorbecke and Wapenaar, 2007;Toxopeus et al, 2008;van Veldhuizen et al, 2008). Interferometry by multidimensional deconvolution as such can be compared with migration deconvolution (Hu et al, 2001;Yu et al, 2006;Zhang and Ulrych, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The interferometric PSF has a lot in common with the resolution function or PSF as we find it in seismic migration (Schuster and Hu, 2000;Thorbecke and Wapenaar, 2007;Toxopeus et al, 2008;van Veldhuizen et al, 2008). Interferometry by multidimensional deconvolution as such can be compared with migration deconvolution (Hu et al, 2001;Yu et al, 2006;Zhang and Ulrych, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lecomte () and Toxopeus et al . () showed that seismic images can be simulated by filtering a geological model with the migration point‐spread function. In a similar way, interferometric images can be simulated by filtering a geological model with the interferometric migration point‐spread function.…”
Section: Illumination Diagnosis In the Image Domainmentioning
confidence: 99%
“…We could replace the grid of point scatterers by any other object to analyse how such an object would be imaged by physical sources or virtual sources. Lecomte (2008) and Toxopeus et al (2008) showed that seismic images can be simulated by filtering a geological model with the migration point-spread function. In a similar way, interferometric images can be simulated by filtering a geological model with the interferometric migration point-spread function.…”
Section: L L U M I N a T I O N D I A G N O S I S I N T H E I M A G mentioning
confidence: 99%
“…For a delta-function source at position x s with wavelet w(ω), S = w(ω)δ(x − x s ), the solution at some receiver location x r can be expressed by equation (3.2.1) of Bleistein et al (2000), which in our notation becomes (Devaney, 1984;Gjøystdal et al, 2002) or resolution function (von Seggern, 1991;Wapenaar, 1997;Chen and Schuster, 1999;Berkhout et al, 2001;Toxopeus et al, 2004Toxopeus et al, , 2008. Lailly (1983) and Tarantola (1984) showed that the gradient or sensitivity of the least-squares error functional is a migration image.…”
Section: Problem Statementmentioning
confidence: 99%